7-2(w-2)=6w-13

Simple and best practice solution for 7-2(w-2)=6w-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-2(w-2)=6w-13 equation:



7-2(w-2)=6w-13
We move all terms to the left:
7-2(w-2)-(6w-13)=0
We multiply parentheses
-2w-(6w-13)+4+7=0
We get rid of parentheses
-2w-6w+13+4+7=0
We add all the numbers together, and all the variables
-8w+24=0
We move all terms containing w to the left, all other terms to the right
-8w=-24
w=-24/-8
w=+3

See similar equations:

| 5-4+7x+1=6x+4 | | x-5÷2=9 | | 5-4+7x+1=4x+4 | | 3m-15+7m-11=14+30 | | 2=-5/3c+9 | | 5c+5=3c+8 | | 2=-5/3c=9 | | 50v+600=1250 | | 4(2d-4)=12 | | 7y=21y^2 | | 2/3x+4/3=1/6x+1/3 | | 1+0.6x=1.4x-0.6 | | 4x-7=2x=+7 | | 17r-12r+r=18 | | 7w+1=7 | | 4w+3w-6w=w+15+2w+3w | | 2x÷3=x÷2+20 | | 2v+8-5v=-2 | | N=10n-N | | 180=10x−11+3x−2+3x+1 | | 12v-3v=45 | | 6x=-2-4 | | 50x2-4050=0 | | 9/11x=3/4 | | x+(2x)+(3x+6)=180 | | X2+5=x+15 | | 1.6x-1.6=6.4 | | 6v+8=-4v | | 33-18=3(x-6) | | 12c-6c=6 | | 2x+3+3x-23=180 | | -21y^2+7y=0 |

Equations solver categories